Hubungan Persepsi Pajak Dan Tanggung Jawab Kepatuhan Wajib Pajak Restoran Di Kota Tangerang - Yulia, Eka Fitri; Kamil, Mustofa; Suhifatullah, M. I. (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
Taxes have an important role in the implementation of development, because regional development is very dependent on the acquisition of local taxes, the optimization of local tax revenues depends on taxpayer compliance. Objectives: (1). To analyze the relationship between tax perception and restaurant taxpayer compliance (2). To analyze the relationship between responsibility and obedience to restaurant taxpayers (3). Analyzing the relationship of responsibility with restaurant taxpayer compliance. Method with quantitative approach. The technique of collecting is through the distribution of questionnaires, survey study documentation. Respondents amounted to 94 people. Analysis using multiple linear regression. The conclusion shows that (1). Tax perception in taxpayer obedience (2). Responsibility with taxpayer obedience 3) Tax perception and citizen responsibility simultaneously with restaurant taxpayer obedience in Tangerang City. Keywords: Tax Perception, Responsibility, Compliance, Restaurant